Fortunately, the milk - Gaiman, Neil.; Young, Skottie (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2013)
While picking up milk for his children's cereal, a father is abducted by aliens and finds himself on a wild adventure through time and space.
Publisher's Weekly, July 2013
Booklist, July 2013
Kirkus Review, July 2013
4.2
3-6
Keywords: Space and time -- Juvenile fiction; Fathers -- Juvenile fiction; Space and time -- Fiction; Fathers -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Space and time -- Fiction; Fathers -- Fiction; Adventure fiction; Humorous fiction; Adventure fiction; Humorous fiction